2020
DOI: 10.1155/2020/9670704
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of Dead Load Shear Force Distribution in Webs of Multicell Inclined Web Box‐Girder Bridge

Abstract: Moment and shear load distribution are important in bridge design. Most existing studies have focused on the distribution of girders under vehicle loading, neglecting the dead load distribution between the webs of multicell box-girders. Through the “Sum of Local Internal Forces” function, the shear force of each web in the multicell box-girder 3D finite element model was extracted and analysed using the dead load shear force distribution factor. The research parameters include the slope of the web, support con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…Yet, the failure manners of the hybrid RCB girders were additionally ductile than in the BFRP RCB girder BF. Moreover, it was found that the crack patterns and failure modes of RCB girders reinforced with mixed steel and BFRP bars in the current study agree well with the observations of many previous research studies carried out on solid RC beams [36]. Through the observations of the current study and the previous ones, it was found that the cracking spacing and width are controlled by the amount of steel and FRP reinforcements.…”
Section: Crack Patterns and Failure Modessupporting
confidence: 89%
“…Yet, the failure manners of the hybrid RCB girders were additionally ductile than in the BFRP RCB girder BF. Moreover, it was found that the crack patterns and failure modes of RCB girders reinforced with mixed steel and BFRP bars in the current study agree well with the observations of many previous research studies carried out on solid RC beams [36]. Through the observations of the current study and the previous ones, it was found that the cracking spacing and width are controlled by the amount of steel and FRP reinforcements.…”
Section: Crack Patterns and Failure Modessupporting
confidence: 89%
“…The dead load shear force i is calculated with the following expression [2]: In conclusion, the authors have established the next affirmations:  for the factor of shear force distribution, in the dead load, the cells number has a higher influence compared with support condition  the side web shear force considering the dead load exceeds a limit value and becomes dangerous for the bridge  the distribution factor of the dead load shear force stays unchanged in the elastic phase [2].…”
Section: Xingwei Xue Et Al (2020) "Numerical Analysis Of Dead Load Sh...mentioning
confidence: 92%
“…Box girder bridges are made up of several "box" type beams which by assembling them, the surface of a section of road is created. Box girder bridges are particularly widespread in cities mainly due to their attractive appearance [1,2]. First box girder bridge, named "The Sclayn", designed by Gustave Magnel, was created over the Mass River in Belgium in 1948.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the total strain crack model, which has many good examples for analysing concrete structures [28][29][30], uses nonlinear three-dimensional finite element analysis (FEA) to model the shear strength concrete beams of EVPRs. e main objectives of this study are as follows:…”
Section: Introductionmentioning
confidence: 99%